2014
DOI: 10.1093/jac/dku359
|View full text |Cite
|
Sign up to set email alerts
|

MLST reveals potentially high-risk international clones of Enterobacter cloacae*

Abstract: Together with the information available in the MLST database, our results suggest that, like Escherichia coli and Klebsiella pneumoniae, E. cloacae harbours clonal lineages of increased epidemic potential that may be associated with resistance spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
109
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 55 publications
8
109
1
Order By: Relevance
“…1). This result is consistent with results from Izdebski et al (2015), who reported very recently a clonal diversity of 97.5% among expanded-spectrum cephalosporin-resistant E. cloacae isolates from Europe and Israel (Izdebski et al, 2015). The discriminatory ability of the different loci, measured as the number of alleles obtained for each gene, varied from 17 (for rpoB and rplB) to 21 (for dnaA) ( Table 1).…”
Section: Mlst and Phylogenetic Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…1). This result is consistent with results from Izdebski et al (2015), who reported very recently a clonal diversity of 97.5% among expanded-spectrum cephalosporin-resistant E. cloacae isolates from Europe and Israel (Izdebski et al, 2015). The discriminatory ability of the different loci, measured as the number of alleles obtained for each gene, varied from 17 (for rpoB and rplB) to 21 (for dnaA) ( Table 1).…”
Section: Mlst and Phylogenetic Analysissupporting
confidence: 90%
“…This result differs from that obtained by Miyoshi-Akiyama et al (2013), reporting the leuS and pyrG alleles as the most polymorphic ones. The result of the nucleotide diversity analysis within the sample, performed on alleles of each MLST gene, demonstrated significant diversity in accordance with the data from Miyoshi-Akiyama et al (2013) and Izdebski et al (2015).…”
Section: Mlst and Phylogenetic Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…These values will underestimate total CPE incidence, because carba penemases also occur in other Enterobacteriaceae, albeit less frequently than in Klebsiella spp. 17 Moreover, the absence of denominator data from eight countries cautions against our ranking of prevalence. Proportions of carbapenemase-positive bacteria considered in this study varied between countries and between the two species under investigation (table 2, table 3).…”
Section: Discussionmentioning
confidence: 99%